Jump start Sass - Giraudel, Hugo; Suzanne, Miriam (SitePoint Pty., 2016)
Get a Jump Start on the popular CSS preprocessor Sass today! Using Sass, you can write your stylesheets in a more concise, dynamic, and readable way, and cut down many of the tedious repetitive tasks that come with writing vanilla CSS. Sass simplifies your stylesheets, adding some useful features missing from CSS. Most importantly, Sass will save you time. This book provides a thorough introduction to Sass for the beginner. In it, you'll learn: What preprocessors are and how they can be useful Installation and getting started Variables, mixins, and functions Loops and conditions Nesting Extend Warnings & errors Project architecture The Sass ecosystem And more!